Protective Effect of the α7 Nicotinic Receptor Agonist PNU-282987 on Dopaminergic Neurons Against 6-Hydroxydopamine, Regulating Anti-neuroinflammatory and the Immune Balance Pathways in Rat - Jiang, Ying; Ma, Huizi; Wang, Xuemei; Wang, Zhan; Yang, Yaqin; Li, Longling; Feng, Tao (Frontiers in Aging Neuroscience, 2021)
Neuroinflammation and inner immune dysfunction are increasingly accepted as important components of the etiopathogenesis of Parkinson’s disease (PD). According to emerging evidence, a7 nicotinic acetylcholine receptor (α7nAChR), a ligand-gated ion channel, plays an important role in inflammatory reactions and is also expressed on the surface of T cells. In particular, regulatory T cells (Tregs) are critical for the maintenance of immunological tolerance. In the present study, we investigated the roles of α7nAChR in inhibiting inflammation and maintaining the immune balance in rats with 6-hydroxydopamine (6-OHDA)-induced lesions and the possible mechanisms regulating the proportion of Tregs in vivo. Adult male Wistar rats (n=90) were subjected to a unilateral injection of 6-OHDA into the left medial forebrain bundle, and PNU-282987, an α7nAChR agonist, was intraperitoneally injected 2 h prior to the induction of lesions by 6-OHDA and again at days 1, 7 and 13 postlesion. Behavioral tests and immunohistochemical staining to detect the expression of tyrosine hydroxylase (TH) in the bilateral substantial nigra (SN) were performed. Subsequently, CD4+ T lymphocytes and the expression of forkhead/winged helix transcription factor p3 (Foxp3, which is a marker of Treg cells) in the SN were also assessed using immunofluorescence staining. The expression of glial fibrillary acidic protein (GFAP) in the SN was determined by performing immunohistochemical staining. Additionally, the protein levels of α7nAChR, extracellular signal-regulated kinase (Erk) phosphorylated-Erk (p-Erk) and Foxp3 in the ventral midbrain were determined using Western blotting, and the relative expression of the TNF-α, IL-1β and IL-10 mRNAs were detected using real-time quantitative reverse transcription-polymerase chain reaction (RT-PCR). We found that PNU-282987 significantly improved the motor deficits induced by 6-OHDA, reduced the loss of TH in the SN, suppressed the overactivation of GFAP+ cells and expression of related inflammatory cytokines, and increased the number of Foxp3+ cells. In addition, we also showed that PNU-282987 significantly increased the protein expression of the a7nAchR, p-Erk, and Foxp3 in 6-OHDA-lesioned rats (p < 0.05). These results indicated that α7nAChR activation could exert an anti-inflammatory effect and participate in the process of modulating the immune balance during 6-OHDA-induced injury, potentially through the α7nAChR/p-Erk/Foxp3 signaling pathway.